2022
DOI: 10.1109/access.2022.3224466
|View full text |Cite
|
Sign up to set email alerts
|

A QoS Aware Cluster Head Selection and Hybrid Cryptography Routing Protocol for Enhancing Efficiency and Security of VANETs

Abstract: Nowadays, VANET (vehicular ad hoc network) is one of the key aspects of developing advanced intelligent transportation systems. Due to its huge mobility and rapid topology alteration, the network exposes to link failure that affects the firmness of the network and causes delay and congestion. Additionally, the dynamic change in the network routing affects the network's security, makes it vulnerable to various attacks, and causes data loss. In order to overcome these drawbacks an efficient and highly secured ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The response provides the client with the desired information. The client then processes the data that was received [13].…”
Section: Handle Systemmentioning
confidence: 99%
“…The response provides the client with the desired information. The client then processes the data that was received [13].…”
Section: Handle Systemmentioning
confidence: 99%
“…This indicates that the proposed technique not reduces power consumption in 5G-based IoMT systems, improves service quality by ensuring that cluster-head is evenly distributed over the network. Jubair, M. A et al [26] demonstrated in this research, we propose a novel routing protocol, QoSC, which combines QoS-aware Cluster Head (CH) selection with hybrid cryptography [QoS-CH]. The QoSC protocol is comprised mostly of two parts: QoS-based CH selection and hybrid cryptography.…”
Section: Background Researchmentioning
confidence: 99%
“…Cluster analysis categorises the areas with the most congestion based on a variety of congestion time factors. In [9], the authors proposed a V2V-based technique for detecting traffic jams that took into account vehicle speed, traffic density, and a rating system for traffic congestion. Shortest path (from scene of accident to hospital) algorithm for ambulance routing was proposed in work [10].…”
Section: Literature Reviewmentioning
confidence: 99%